Multidisciplinary Approach to Obesity - Berna Bulut Çakmak; Aslýhan Dönmez (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Obesity is a world wide public health problem which increases morbidity and mortality. A multidiciplinary approach is increasingly becoming important for treatment of obesity. Pharmacological agents, sergery, and cognitive behavioral terapy (CBT) are the recommended treatment approaches. In this review, these treatment modalities are reviewed. In CBT of obesity, the dysfunctional thoughts and behaviors which prevent the person for losing weight or doing exercise opr which cause gaining back the lost weight are identified, and specific techniques to change these thoughts and behaviors are thought. It may be used as an individiual therapy, but it may also be more effective when used as a group psychotherapy. In this article, the CBT techniques used in obesity treatment are summarized. [JCBPR 2014; 3(3.000): 142-149]